Penyuluhan Pemanfaatan Herbal Pencegah Tinea Pedis Pada Masyarakat di Wilayah Rawan Banjir - lia Yulia Budiarti; Siti Kaidah; Husnul Khatimah; Erida Widyamala (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2021)
Tinea pedis is a contagious disease caused by fungal infection and is often experienced by refugees, due to delays in treatment during floods. Kelurahan Sungai Lulut is the largest area, which was affected by the flood disaster in Banjarmasin city in January 2021. Many refugees from this area have tinea pedis disorder, so knowledge is needed for the community to recognize and utilize medicinal plants, which exist in the community along the river. and in flood prone areas. This PKM activity aims to provide counseling about types of herbs and their use to prevent tinea pedis disease in the community in Kelurahan Sungai Lulut. Extension activities are carried out offline with the target partners are housewives. Evaluation is assessed based on answers to the questionnaire before and after PKM activities. The results of the activity showed that more than 90% of the target partners could identify the types of herbs that could be used to treat tinea pedis. The conclusion of outreach activities can increase the knowledge of target partners in recognizing and utilizing types of herbs to prevent tinea pedis. It is hoped that the target partners who have received counseling can practice it, and similar activities can be further developed in other communities.